Hydrogel with high strength and high ionic conductivity as well as preparation method and application thereof

By combining glyoxaldehyde-modified acrylamide with polyvinyl alcohol to form a hydrogel with a dual network structure, the problem of difficult to achieve both mechanical properties and electrical conductivity of existing hydrogel electrolytes is solved, and a hydrogel with high strength and high ionic conductivity is achieved, which is suitable for flexible electronic equipment.

CN119875151AActive Publication Date: 2025-04-25WUHAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510009897.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-25
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

It is difficult to obtain both the existing hydrogel electrolytes between improving mechanical properties and ionic conductivity, resulting in the problems of insufficient mechanical strength and poor conductivity when used in flexible electronic devices.

Method used

Acrylamide is modified by glyoxal to form glyoxal grafted polyacrylamide, and combined with polyvinyl alcohol, and cross-linking of dynamic borate ester and hydrogen bonds to form a semi-interpenetrating polymer network to synthesize a hydrogel with a dual network structure.

Benefits of technology

The high ionic conductivity and high mechanical properties of the hydrogel are achieved, the tensile strength and modulus are significantly improved, and good conductivity and tensile properties are maintained after the bending cycle, showing strong fatigue resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875151A_ABST
    Figure CN119875151A_ABST
Patent Text Reader

Abstract

The invention discloses high-strength and high-ionic-conductivity hydrogel as well as a preparation method and application thereof, and belongs to the technical field of high polymer materials. The method comprises the following steps: S1, dissolving acrylamide in deionized water, adding an initiator and glyoxal to obtain a mixed solution, and then carrying out grafting reaction under the condition that the pH value is 3-4 to obtain a glyoxal grafted polyacrylamide solution; s2, adding a polyvinyl alcohol solution into the glyoxal grafted polyacrylamide solution, adding a boric acid aqueous solution while stirring, adding a cross-linking agent after reaction, stirring and dissolving, transferring into a mold, and heating to obtain the hydrogel. The hydrogel patch prepared by the method has excellent ionic conductivity and high mechanical strength, and the problem that high mechanical strength and excellent conductivity of hydrogel in the prior art are difficult to achieve at the same time is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a hydrogel with high strength and high ion conductivity and a preparation method and application thereof. Background Art

[0002] Flexible wearable electronic devices have attracted widespread attention from academia and industry, but problems such as insufficient mechanical strength and poor conductivity have seriously hindered the application and development of these devices. Traditional liquid electrolytes are prone to leakage, have low electrochemical stability, and evaporate quickly. Hydrogel electrolytes are composed of polymer networks and electrolyte solutions. They are quasi-solid electrolytes that can retain a large amount of ionic solution without leakage while having good flexibility and conductivity. These properties make hydrogels an ideal electrolyte material for flexible electronic devices and can significantly improve the overall performance of these devices.

[0003] The main challenges faced by existing hydrogel electrolytes include insufficient mechanical properties and low ionic conductivity caused by insufficient cross-linking. Therefore, current research focuses on improving the mechanical properties and ionic conductivity of hydrogels through various methods. Common hydrogel electrolytes include those based on polyacrylamide and polyvinyl alcohol, which conduct electricity by promoting the directional migration of freely mobile ions in the gel network when an electric field is applied. Recently, flexible hydrogel electrolytes with a variety of new designs have been reported. For example, the addition of proteins to the composite gel has been shown to effectively enhance adhesion, improve low-temperature resistance, and retain a large amount of electrolyte solution. However, the mechanical properties provided by these composite gels are often relatively limited. The combination of chemical coordination and physical cross-linking has been shown to significantly improve the mechanical properties. For example, by incorporating Fe 3+ The ions were mixed with polyvinyl acetate (PVAA) / polyacrylamide (PAM) hydrogel to form a double network hydrogel system with high tensile strength, compressibility and self-healing properties. In addition, the researchers also synthesized hydrogel electrolytes by crosslinking carboxyl-modified polyvinyl alcohol with COO-Fe bonds in the presence of Zn(NO3)2 and MnSO4, resulting in improved mechanical properties due to the strengthening of the crosslinked network. However, ionic conductivity is also an important performance indicator for electrolyte materials. Achieving a balance between improving mechanical properties and ionic conductivity remains a huge challenge for hydrogel electrolytes in flexible electronics. The elastic modulus reflects the ability of a material to resist deformation when subjected to stress. The larger the elastic modulus, the smaller the elastic deformation of the material under the same stress. In the hydrogel patch battery, the hydrogel is in full contact with the electrode ink. If the hydrogel is excessively deformed by stretching or compression, it may cause the electrode ink to break and fall off. Therefore, the hydrogel requires a high elastic modulus, and the elastic modulus of the wearable drug delivery patch and its mechanical properties under bending fatigue are particularly important. Summary of the invention

[0004] In view of the above shortcomings of the prior art, one of the objects of the present invention is to provide a method for preparing a high-strength, high-ionic conductivity hydrogel. The prepared hydrogel patch has both excellent ionic conductivity and high mechanical strength, solving the problem that it is difficult to achieve both high mechanical strength and excellent conductivity in the prior art hydrogel.

[0005] The above object of the present invention is achieved through the following technical solutions:

[0006] A method for preparing a hydrogel with high strength and high ionic conductivity comprises the following steps:

[0007] S1. acrylamide was dissolved in deionized water, an initiator and glyoxal were added to obtain a mixed solution, and then a grafting reaction was carried out at a pH of 3 to 4 to obtain a glyoxal-grafted polyacrylamide solution;

[0008] S2. Add polyvinyl alcohol solution to the glyoxal grafted polyacrylamide solution, add boric acid aqueous solution while stirring, add cross-linking agent after reaction, stir and dissolve, transfer to a mold, and heat to obtain a hydrogel.

[0009] The present invention first adopts glyoxal to modify acrylamide, an aldehyde group in glyoxal reacts with the amide group in acrylamide to generate hydroxyl, and polymerization is initiated simultaneously, and its unreacted aldehyde group is then introduced into the segment of polyacrylamide to obtain glyoxal-polyacrylamide, and the number of hydroxyl groups on the molecular chain can be increased by adopting glyoxal to modify acrylamide, and the crosslinking between polyacrylamide and boric acid and polyvinyl alcohol can be effectively promoted. Then, glyoxal-grafted polyacrylamide and polyvinyl alcohol are used as raw materials, and a semi-interpenetrating polymer network is formed by combining dynamic borate and hydrogen bond crosslinking, and a hydrogel of double network structure is successfully synthesized. The prepared hydrogel has high ionic conductivity, tensile strength and modulus, and not only conductivity is significantly improved, but also mechanical properties are enhanced, and the problem that the high mechanical strength of existing conductive hydrogel and excellent conductivity are difficult to obtain at the same time is solved. In addition, the hydrogel can still maintain its conductivity and tensile properties after experiencing thousands of bending cycles, and shows good fatigue resistance. In mice, the drug delivery patch prepared by this hydrogel has also confirmed its effective transdermal drug delivery effect.

[0010] Preferably, the concentration of acrylamide in the mixed solution is 30%wt~50%wt, and the concentration of glyoxal is 9%wt~15%wt.

[0011] Preferably, the glyoxal is a glyoxal aqueous solution with a concentration of 30%wt~50%wt, and the mass ratio of the glyoxal aqueous solution to acrylamide is (1~6):(2~8).

[0012] Preferably, the initiator is potassium persulfate and / or ammonium persulfate, and the mass of the initiator is 0.1% to 2.5% of the mass of acrylamide.

[0013] Preferably, the mass ratio of the glyoxal-grafted polyacrylamide solution to the polyvinyl alcohol solution is (3-9):(3-10), and the concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 5%wt-10%wt.

[0014] More preferably, the mass ratio of the glyoxal-grafted polyacrylamide solution to the polyvinyl alcohol solution is (3-9):(3-7), and the concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 5%wt-10%wt.

[0015] Preferably, the mass ratio of the glyoxal grafted polyacrylamide solution to the boric acid aqueous solution is (3-9):(2-8), and the concentration of boric acid in the boric acid aqueous solution is 2%wt-6%wt.

[0016] More preferably, the mass ratio of the glyoxal grafted polyacrylamide solution to the boric acid aqueous solution is (3-9):(4-6), and the concentration of boric acid in the boric acid aqueous solution is 2%wt-6%wt.

[0017] Preferably, in step S1, the grafting reaction is carried out under the following conditions: stirring at 25-45° C. and 100-300 rpm for 1-5 h.

[0018] Preferably, in step S2, the reaction temperature is 10-50°C, and the reaction time is 1.5-5h; the heating temperature is 30-70°C, and the reaction time is 1-5h.

[0019] Another object of the present invention is to provide a hydrogel with high strength and high ionic conductivity prepared by the preparation method.

[0020] Another object of the present invention is to provide the use of the high-strength and high-ionic conductivity hydrogel in flexible wearable devices, drug carriers or biological tapes.

[0021] The present invention further provides a wearable drug introduction hydrogel patch using the hydrogel as an electrolyte material, which is prepared by the following method:

[0022] M1. The zinc powder, ZnO, carbon black, PVDF and NMP solvent are uniformly mixed to prepare a zinc electrode ink, and the ink is deposited on the surface of the copper foil to obtain a negative electrode;

[0023] M2. Ni(OH)2, carbon black and PVDF are uniformly mixed to form a nickel electrode ink, and the ink is deposited on the surface of a copper foil to obtain a positive electrode;

[0024] M3. After the hydrogel is fully soaked in KOH electrolyte, it is assembled with the positive electrode, negative electrode, medical tape and medical cotton loaded with drugs into an ion introduction patch.

[0025] Compared with the prior art, the present invention is beneficial in that:

[0026] (1) The hydrogel prepared by the present invention exhibits a high ionic conductivity, which reaches 11.33 S / m after ion adsorption. It also has excellent mechanical properties, with a tensile strength of 491.27 kPa and a modulus of 1066.11 kPa, and has excellent mechanical properties.

[0027] (2) After 1000 bending cycles, the hydrogel of the present invention can still maintain good conductivity and tensile properties, showing strong anti-fatigue properties.

[0028] (3) The ion introduction patch made of the hydrogel of the present invention exhibits an effective transdermal drug delivery effect in mice. The transdermal drug delivery experiment conducted on mouse skin of the present invention shows that ion penetration can effectively improve drug permeability. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The swelling condition of the hydrogel prepared by the present invention in the electrolyte; wherein, Figure 1 (A) is the swelling of GB4P5 gel in 0-5 mol / L KOH solution. Figure 1 (B) shows the swelling of six gels in 1 mol / L KOH solution. Figure 1 (C) is the mass retention capacity of GB4P5 gel after swelling in KOH solutions of different concentrations for 24 hours. Figure 1 (D) is the mass retention capacity of the six gels after swelling in 1 mol / L KOH solution for 24 h. Figure 1 (E) is the optical image of GB4P5 hydrogel before swelling. Figure 1 (F) is the optical image of GB4P5 hydrogel after swelling in 1 mol / L KOH solution for 24 h;

[0030] Figure 2 The mechanical properties of the hydrogel prepared by the present invention are shown in FIG. Figure 2 (A) is the tensile stress-strain curve of dumbbell-shaped hydrogel; Figure 2 (B) is the modulus of the hydrogel at break when stretched; Figure 2 (C) is the tensile stress-strain curve of the gel sample after bending 1000 times; Figure 2 (D) is the retention rate of the maximum breaking strength and maximum strain value of the four gels before and after bending; Figure 2 (E) is the compressive stress-strain curve of the block hydrogel; Figure 2 (F) is the compression stress-strain curve of GB4P5 gel after 100 cycles of compression;

[0031] Figure 3 The conductive properties of the hydrogel prepared by the present invention; wherein, Figure 3 (A) is the electrochemical impedance spectroscopy of the hydrogel. Figure 3 (B) is the ionic conductivity of the hydrogel, Figure 3 (C) is the resistance change rate curve of GB6P3 during continuous bending cycle from 0s to 1800s. Figure 3 (D) is the resistance change rate curve of GB6P3 during continuous bending cycle from 1000s to 1050s;

[0032] Figure 4 is a schematic diagram of the patch of the present invention; wherein, Figure 4 (A) is a schematic diagram of the structure of the ion introduction patch of the present invention, Figure 4 (B) is a schematic diagram of the patch of the present invention attached to the skin surface of a human arm, Figure 4 (C) Schematic diagram of simulating in vitro transdermal experiments using diffusion cell experiments;

[0033] Figure 5 is the electrochemical performance of the patch battery of the present invention; wherein, Figure 5 (A) is the electrochemical impedance spectrum of the patch battery of the present invention, Figure 5 (B) is the charge and discharge curve of the patch battery at different current densities in the voltage window of 0-1.2V. Figure 5 (C) is the battery at 1mA / cm 2 Constant current charge and discharge curve under ;

[0034] Figure 6 The drug delivery effect of the ion introduction patch of the present invention; wherein, Figure 6 (A) is the drug penetration on mouse skin, Figure 6 (B) is the effect of different substances on the permeability. Figure 6 (C) is the drug penetration into pig skin;

[0035] Wherein: 1. Skin; 2. Ion introduction patch; 201. Positive and negative electrodes; 202. Hydrogel electrolyte; 203. Medical tape; 204. Medical cotton loaded with drugs; 3. Air outlet; 4. Vertical diffusion cell; 5. Ultrapure water. DETAILED DESCRIPTION

[0036] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The present invention provides a method for preparing a hydrogel with high strength and high ionic conductivity, comprising the following steps:

[0038] S1. acrylamide was dissolved in deionized water, an initiator and glyoxal were added to obtain a mixed solution, and then a grafting reaction was carried out at a pH of 3 to 4 to obtain a glyoxal-grafted polyacrylamide solution;

[0039] S2. Add polyvinyl alcohol solution to the glyoxal grafted polyacrylamide solution, add boric acid aqueous solution while stirring, add cross-linking agent after reaction, stir and dissolve, transfer to a mold, and heat to obtain a hydrogel.

[0040] In step S1, the concentration of acrylamide in the mixed solution is 30%wt~50%wt, and the concentration of glyoxal is 9%wt~15%wt.

[0041] In step S1, the glyoxal is a glyoxal aqueous solution with a concentration of 30%wt-50%wt, and the mass ratio of the glyoxal aqueous solution to acrylamide is (1-6):(2-8).

[0042] In step S1, the initiator is potassium persulfate and / or ammonium persulfate, and the mass of the initiator is 0.1% to 2.5% of the mass of acrylamide.

[0043] In step S2, the mass ratio of the glyoxal-grafted polyacrylamide solution to the polyvinyl alcohol solution is (3-9):(3-10), and the concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 5%wt-10%wt.

[0044] In step S2, the mass ratio of the glyoxal grafted polyacrylamide solution to the boric acid aqueous solution is (3-9):(2-8), and the concentration of boric acid in the boric acid aqueous solution is 2%wt-6%wt.

[0045] In step S1, the grafting reaction conditions are: stirring at 25-45° C. and 100-300 rpm for 1-5 h.

[0046] In step S2, the reaction temperature is 10-50°C, and the reaction time is 1.5-5h; the heating temperature is 30-70°C, and the reaction time is 1-5h.

[0047] The method for preparing a high-strength, high-ionic conductivity hydrogel according to a specific embodiment of the present invention comprises the following steps:

[0048] S1. Take 3 g of acrylamide and dissolve it in 6 ml of deionized water, add 10 mg of potassium persulfate and 3 g of glyoxal (40%wt) solution, and stir at 300 rpm for 1 h at pH = 3-4 and 45°C to obtain glyoxal-grafted polyacrylamide (GPAM) solution;

[0049] S2. Take 4 g of GPAM solution, add an appropriate amount of polyvinyl alcohol (PVA) (8%wt) solution at a stable rotation speed of 400 rpm, then slowly add an appropriate amount of H3BO3 (4%wt) solution, stir at 50°C for 1.5 h, then add 5 mg of N,N'-methylenebisacrylamide (MBA), stir to dissolve it evenly to obtain a mixture; the mixture after removing bubbles is immediately transferred to a mold of a specific shape, and heated in an oven at 70°C for 1.5 h to obtain GPAM-B-PVA hydrogel samples of different shapes.

[0050] Examples 1 to 6 all prepared hydrogels according to the above method, the only difference being that the masses of the polyvinyl alcohol solution and the H3BO3 solution in step S2 were different. The masses of the polyvinyl alcohol solution and the H3BO3 solution added in each example are shown in Table 1.

[0051] Table 1

[0052]

[0053] Figure 1 The swelling condition of the hydrogel prepared by the present invention in the electrolyte. Figure 1 (A) is the swelling of GB4P5 gel in 0-5 mol / L KOH solution. Figure 1 (B) shows the swelling of six gels in 1 mol / L KOH solution. Figure 1 (A) and Figure 1 (B) It can be seen that the swelling rate of the hydrogel decreases in high-concentration electrolyte. The increase in H3BO3 and PVA content will increase the cross-linking density and limit the swelling, indicating that the swelling behavior of the hydrogel is affected by the electrolyte concentration and its own cross-linking structure. Figure 1 (C) is the mass retention capacity of GB4P5 gel after swelling in KOH solutions of different concentrations for 24 hours. Figure 1 (D) is the mass retention capacity of the six gels after swelling in 1 mol / L KOH solution for 24 h. Figure 1 (C) and Figure 1(D) It can be seen that the hydrogel exhibits strong ion retention ability in high concentration KOH solution, and the content of H3BO3 and PVA has little effect on the ion retention ability of the hydrogel; Figure 1 (E) is the optical image of GB4P5 hydrogel before swelling. Figure 1 (F) is the optical image of GB4P5 hydrogel after swelling in 1 mol / L KOH solution for 24 h. Figure 1 (E) and Figure 1 (F) It can be seen that the width of the gel before swelling was 1.5 cm, and the width after swelling was about 1.91 cm, an increase of about 27.3%. The size of the hydrogel increased significantly after swelling.

[0054] The mechanical properties of hydrogels, especially the tensile and compressive properties, are crucial for their applications in flexible electronic devices. Figure 2 The mechanical properties of the hydrogel prepared by the present invention are shown in FIG. Figure 2 (A) is the tensile stress-strain curve of dumbbell-shaped hydrogel; Figure 2 (B) is the modulus of the hydrogel at break when stretched; Figure 2 (C) is the tensile stress-strain curve of the gel sample after bending 1000 times; Figure 2 (D) is the retention rate of the maximum breaking strength and maximum strain value of the four gels before and after bending; Figure 2 (E) is the compressive stress-strain curve of the block hydrogel; Figure 2 (F) is the compression stress-strain curve of GB4P5 gel after 100 cycles of compression; it can be seen from the figure that the amount of boric acid and polyvinyl alcohol affects the tensile properties of the hydrogel, among which GB0P5 shows lower tensile stress and elongation due to the lack of borate ester crosslinking, while GB4P5 shows the highest fracture strength and modulus due to the high crosslinking density between GPAM and PVA chains. The hydrogel also shows good fatigue resistance and can maintain its tensile and compressive strength even after multiple bending and compression cycles. These properties make hydrogels ideal materials for flexible electronic devices, able to withstand repeated stress in daily use without losing performance.

[0055] The internal resistance and ionic conductivity of the hydrogels were measured by electrochemical impedance spectroscopy (EIS). Figure 3 The conductive properties of the hydrogel prepared by the present invention; wherein, Figure 3 (A) is the electrochemical impedance spectroscopy of the hydrogel. Figure 3 (B) is the ionic conductivity of the hydrogel, Figure 3 (A) and Figure 3(B) It can be seen that the conductivity of the hydrogel is not only affected by the number of adsorbed ions, but also related to the characteristics of the pore size as an ion transmission channel; although GB4P5 has the strongest adsorption capacity, its thin pore wall may affect the direction of ion movement, while the thick wall structure and large pores of GB6P7 are conducive to the formation of stable ion channels, thereby promoting the directional movement of ions; GB6P5 exhibits the highest conductivity of 11.46 S / m. Figure 3 (C) is the resistance change rate curve of GB6P3 during continuous bending cycle from 0s to 1800s. Figure 3 (D) is the resistance change rate curve of GB6P3 during continuous bending cycle from 1000s to 1050s; Figure 3 (C) and Figure 3 (D) It can be seen that during the continuous bending cycle, the resistance change rate of the hydrogel remains within 15%, showing good mechanical properties and resistance stability, but long-term bending may cause partial damage to the ion transport channel and gradually increase the resistance value.

[0056] This embodiment also provides a method for preparing an ion introduction patch, comprising the following steps:

[0057] M1. The zinc powder, ZnO, carbon black, PVDF and NMP solvent were uniformly mixed to prepare a zinc electrode ink, and the ink was printed on the surface of the copper foil to obtain a negative electrode;

[0058] M2. Ni(OH)2, carbon black and PVDF are uniformly mixed to form a nickel electrode ink, and the ink is printed on the surface of a copper foil to obtain a positive electrode;

[0059] M3. A film of GB6P3 hydrogel is fully soaked in 4 M KOH electrolyte to obtain a hydrogel electrolyte 202, which is then assembled into an ion introduction patch 2 (such as Figure 4 A), and then stick the patch on the surface of the skin 1 of the human arm (as shown in Figure 4 B); then the diffusion cell experiment was used to simulate the in vitro transdermal experiment. The experimental schematic diagram is shown in Figure 4 As shown in C, the skin 1 with the ion introduction patch 2 is placed on a device with an air outlet 3 and a vertical diffusion pool 4, and the vertical diffusion pool 4 is filled with ultrapure water 5.

[0060] Figure 5 is the electrochemical performance of the patch battery of the present invention; wherein, Figure 5 (A) is the electrochemical impedance spectrum of the patch battery of the present invention, Figure 5 (B) is the charge and discharge curve of the patch battery at different current densities in the voltage window of 0-1.2V. Figure 5(C) is the battery at 1mA / cm 2 Constant current charge and discharge curve under Figure 5 As can be seen from (A), the equivalent internal resistance of the Ni-Zn battery (including electrode resistance, electrolyte resistance and contact resistance) is only 0.37Ω. This is due to the effective adsorption of KOH electrolyte by the hydrogel, which increases the internal conductivity of the gel. Figure 5 (B) and Figure 5 (C) It can be seen that the charge and discharge curves of different current densities are roughly similar in shape, and both have relatively obvious charge and discharge platforms, indicating that a reversible redox reaction occurs during the charge and discharge process.

[0061] Figure 6 The drug delivery effect of the ion introduction patch of the present invention; wherein, Figure 6 (A) is the drug penetration on mouse skin, Figure 6 (B) is the effect of different substances on the permeability. Figure 6 (C) is the amount of drug permeation on pig skin; as can be seen from the figure, iontophoresis therapy uses low-resistance patches to effectively improve the efficiency of drug transdermal delivery. Experiments show that its efficiency far exceeds passive diffusion, and certain substances such as potassium chloride can further enhance the effect. This method shows great potential in the field of drug delivery.

[0062] Example 7

[0063] The method for preparing the high-strength and high-ionic conductivity hydrogel of this embodiment comprises the following steps:

[0064] S1. Dissolve 3 g of acrylamide in 6 ml of deionized water, add 10 mg of potassium persulfate, and stir at 300 rpm for 1 h at pH = 3-4 and 45°C to obtain a polyacrylamide (PAM) solution.

[0065] S2. Take 4 g of PAM solution, add 3 g of polyvinyl alcohol (PVA) (8%wt) solution at a steady rotation speed of 400 rpm, then slowly add 6 g of H3BO3 (4%wt) solution, stir at 50°C for 1.5 h, then add 5 mg of N,N'-methylenebisacrylamide (MBA), stir to dissolve it evenly to obtain a mixture; the mixture after removing bubbles is immediately transferred to a mold of a specific shape, and heated in an oven at 70°C for 1.5 h to obtain PAM-B-PVA hydrogel samples of different shapes.

[0066] That is, Example 7 is substantially the same as Example 6, and the only difference is that glyoxal is not added in step S1.

[0067] Compared with GB6P3 hydrogel, the hydrogel obtained in this comparative example has poorer ability to adsorb ions, which leads to lower ionic conductivity, which is only 2.16S / m; in addition, the mechanical properties of the hydrogel in this comparative example are also worse, with a tensile strength of 102.25 kPa and a modulus of 248.42 kPa.

[0068] Example 8

[0069] The method for preparing the high-strength and high-ionic conductivity hydrogel of this embodiment comprises the following steps:

[0070] S1. Take 8 g of acrylamide and dissolve it in 6 ml of deionized water, add 50 mg of potassium persulfate and 6 g of glyoxal (40%wt) solution, and stir at 300 rpm for 1 h at pH = 3-4 and 35°C to obtain a glyoxal-grafted polyacrylamide (GPAM) solution;

[0071] S2. Take 9 g of GPAM solution, add 5 g of polyvinyl alcohol (PVA) (8%wt) solution at a steady rotation speed of 600 rpm, then slowly add 6 g of H3BO3 (4%wt) solution, stir at 50°C for 5 h, then add 5 mg of N,N'-methylenebisacrylamide (MBA), stir to dissolve it evenly to obtain a mixture; the mixture after removing bubbles is immediately transferred to a mold of a specific shape, and heated in an oven at 30°C for 5 h to obtain GPAM-B-PVA hydrogel samples of different shapes.

[0072] Example 9

[0073] The method for preparing the high-strength and high-ionic conductivity hydrogel of this embodiment comprises the following steps:

[0074] S1. Take 2g acrylamide and dissolve it in 1ml deionized water, add 10mg potassium persulfate and 1g glyoxal (40%wt) solution, and stir at a steady speed of 100 rpm for 1h at pH=3-4 and 25℃ to obtain glyoxal-grafted polyacrylamide (GPAM) solution;

[0075] S2. Take 3 g of GPAM solution, add 5 g of polyvinyl alcohol (PVA) (8%wt) solution at a steady rotation speed of 100 rpm, then slowly add 6 g of H3BO3 (4%wt) solution, stir at 10°C for 5 h, then add 5 mg of N,N'-methylenebisacrylamide (MBA), stir to dissolve it evenly to obtain a mixture; the mixture after removing bubbles is immediately transferred to a mold of a specific shape, and heated in an oven at 30°C for 5 h to obtain GPAM-B-PVA hydrogel samples of different shapes.

[0076] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a hydrogel with high strength and high ionic conductivity, characterized in that: The following steps are involved: S1. acrylamide was dissolved in deionized water, an initiator and glyoxal were added to obtain a mixed solution, and then a grafting reaction was carried out at a pH of 3 to 4 to obtain a glyoxal-grafted polyacrylamide solution; S2. Add polyvinyl alcohol solution to the glyoxal grafted polyacrylamide solution, add boric acid aqueous solution while stirring, add cross-linking agent after reaction, stir and dissolve, transfer to a mold, and heat to obtain a hydrogel.

2. The method for preparing a hydrogel with high strength and high ionic conductivity according to claim 1, characterized in that: The concentration of acrylamide in the mixed solution is 30%wt-50%wt, and the concentration of glyoxal is 9%wt-15%wt.

3. The method for preparing a hydrogel with high strength and high ionic conductivity according to claim 1, characterized in that: The glyoxal is a glyoxal aqueous solution with a concentration of 30%wt~50%wt, and the mass ratio of the glyoxal aqueous solution to acrylamide is (1~6):(2~8).

4. The method for preparing a hydrogel with high strength and high ionic conductivity according to claim 1, characterized in that: The initiator is potassium persulfate and / or ammonium persulfate, and the mass of the initiator is 0.1% to 2.5% of the mass of acrylamide.

5. The method for preparing a hydrogel with high strength and high ionic conductivity according to claim 1, characterized in that: The mass ratio of the glyoxal grafted polyacrylamide solution to the polyvinyl alcohol solution is (3-9):(3-10), and the concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 5%wt-10%wt.

6. The method for preparing a hydrogel with high strength and high ionic conductivity according to claim 1, characterized in that: The mass ratio of the glyoxal grafted polyacrylamide solution to the boric acid aqueous solution is (3-9):(2-8), and the concentration of boric acid in the boric acid aqueous solution is 2%wt-6%wt.

7. The method for preparing a hydrogel with high strength and high ionic conductivity according to claim 1, characterized in that: In step S1, the grafting reaction conditions are: stirring at 25-45° C. and 100-300 rpm for 1-5 h.

8. The method for preparing a hydrogel with high strength and high ionic conductivity according to claim 1, characterized in that: In step S2, the reaction temperature is 10-50°C, and the reaction time is 1.5-5h; the heating temperature is 30-70°C, and the reaction time is 1-5h.

9. A hydrogel with high strength and high ionic conductivity prepared by the method according to any one of claims 1 to 8.

10. Use of the high-strength and high-ionic-conductivity hydrogel prepared by the method according to any one of claims 1 to 8 in flexible wearable devices, drug carriers or biological tapes.

Citation Information

Patent Citations

  • PAAm / PVA dual-network hydrogel and preparation method thereof

    CN104693456A

  • Production method of environment-friendly chlorine-free polyacrylamide wet strength agent and application thereof to papermaking

    CN109749012A

  • Preparation method of PVA / PAM composite hydrogel

    CN113150325A

  • Modified hydrogel adsorbent as well as preparation method and application thereof

    CN118317829A

  • PVA hydrogels having improved creep resistance, lubricity, and toughness

    US20100210752A1